Securing the Brisbane 2014 G20 in the wake of theToronto 2010 G20: ‘failure-inspired’ learning in public order policing - Molnar, Adam (The British journal of criminology, 2019)
Extending inquiries into the dynamics underpinning the ‘iterative’ development of security governance at mega-events, this article explores practices of knowledge sharing and policy transfer at major political summits. Through detailed interviews with police involved in the Toronto 2010 G20 and the Brisbane 2014 G20 summits, and through analysing supporting documentation, we examine the ways in which police interpret past events, as either ‘failures’ or ‘successes’, specifically in the context of public order policing. The article extends insights into how such perceptions are facilitated through transnational exchanges, particularly where event-related ‘failures’ might be considered as a benchmark for iterative policy developments. We explain this process as a form of ‘failure-inspired social learning’ that questions the effectiveness, norms and legitimacy of established policies, practices and institutions involved in security governance, which can influence future transformations in global ‘best practices’.